Analisis Kinerja Keuangan Menggunakan Rasio Likuiditas, Solvabilitas, dan Aktivitas pada Badan Usaha Milik Desa (Bum Desa) Tridadi Makmur Tahun 2018-2020 - Sutarni Sutarni; Putri Natalia Maharati (Studi Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study aims to analyze the financial performance of Tridadi Makmur Village-Owned Enterprises (BUM Desa) in 2018-2020 using financial ratios in the form of liquidity, solvency, and activity ratios. The research method used is a quantitative descriptive method, using secondary data in the form of financial statements from the Tridadi Makmur Village BUM. Methodology: The sample in this study is Tridadi Makmur's balance sheet and income statement (BUM Desa) for the 2018-2020 period which was carried out using the purposive sampling, data acquisition technique that is by using the method of documentation, interviews, and literature study. method.The data analysis method used is descriptive analysis techniques. Results: The financial performance of Tridadi Makmur Village BUM from 2018 to 2020 based on the current ratio analysis resulted in a very good figure of 210.6%. Based on the results of the quick ratio analysis analysis, it produced a fairly good figure with an average of 167.2%. Based on the results of the cash ratio analysis analysis, it produces a figure that is categorized as bad, namely with an average of 35.0%. Based on the results of the analysis of the debt to asset ratio analysis, it produces a very good figure, namely with an average of 25.5%. Based on the results of the analysis of the debt to equity ratio analysis, it produces a very good categorized figure, namely with an average of 34.3%. Based on the results of the analysis of the debt to equity ratio analysis, it produces a very good categorized figure, namely with an average of 34.3%. Based on the results of the analysis of the total asset turnover ratio (total asset turnover) produced a figure that was categorized as bad, namely with an average of 0.64 times. Limititaions: This study found that from various financial ratio analyzes used, the debt-to-asset ratio and debt-to-equity ratio were categorized as being in a very good position compared to the total asset turnover ratio ( total asset turnover). Contribution: This research is expected to increase knowledge about how village-owned enterprises (BUM Desa) in particular can improve governance and how to manage finances according to the type of business being run.